The Roles of Fluid Intelligence and Emotional Intelligence in Affective Decision-Making During the Transition to Early Adolescence - Li, Danfeng; Wu, Mengli; Zhang, Xingli; Wang, Mingyi; Shi, Jiannong (Frontiers in Psychology, 2020)
The current study mainly explored the influence of fluid intelligence (IQ) and emotional intelligence (EI) on affective decision-making from a developmental perspective, specifically, during the transition from childhood into early adolescence. Meanwhile, their age-related differences in affective decision-making were explored. A total of 198 participants aged 8-12 completed the Iowa Gambling Task (IGT), the Cattell’s Culture Fair Intelligence Test and the Trait Emotional Intelligence Questionnaire-Child Form. Based on the net scores of IGT, the development of affective decision-making ability did not increased monotonically with age, and there was a developmental trend of an impaired IGT performance in early adolescence (aged 11-12), especially in the early learning phase (first 40 trials) of the IGT. More importantly, IQ and EI played different roles for children and early adolescents: IQ and EI jointly predicted the IGT performance for 8-10 year-old children, whereas only EI contributed to the IGT performance of 11-12 year-old early adolescents. The present study extends the evidence how cognitive processing and emotional processing interact in affective decision-making from the developmental perspective. Furthermore, it provides insights of future research and intervention with early adolescents’ poor affective decision-making.